Laminated material for lid
The laminate for lids addresses the issues of content adhesion and heat damage by incorporating a barrier layer, heat seal layer, and content adhesion prevention layer, along with a stress relaxation layer to maintain seal integrity and prevent particle detachment.
Patent Information
- Application Number
- JP2024144288
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-15
- Filing Date
- 2024-08-26
- Publication Date
- 2025-03-28
AI Technical Summary
Existing lid laminates for containers with semi-solid or liquid contents face issues with content adhesion to the lid and heat damage to the content adhesion prevention layer during heat sealing, especially during long-distance transportation where vibrations can cause weak sealing.
A laminate for lids comprising a substrate layer with a barrier layer of deposited metal or metal oxide (0.02 to 2 μm thick), a heat seal layer, and a content adhesion prevention layer formed by hydrophobic fine particles, which includes a stress relaxation layer to maintain seal strength and prevent particle detachment.
The laminate effectively prevents content adhesion to the lid while maintaining barrier properties and reducing heat damage to the content adhesion prevention layer, even under conditions of vibration and temperature changes during transportation.
Smart Images

Figure 2025043284000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate for lids, and more particularly to a laminate for lids used to make lids that seal the openings of containers containing contents such as milk and dairy products (both unprocessed and processed) such as cream and yogurt, liquid foods such as soups and baby foods, and seasonings such as sauces and dressings.
[0002] In this specification, the term "aluminum" includes aluminum alloys as well as pure aluminum. [Background technology]
[0003] As a package for hermetically storing the above-mentioned semi-solid (fluid) or liquid contents, a package consisting of a container with an opening at the top and a lid whose outer periphery is heat-sealed to the periphery of the opening of the container so as to cover the opening of the container is widely used. However, such a package has a problem in that the contents adhere to the inner surface of the lid.
[0004] A known example of a lid laminate that forms a lid and solves these problems is the lid laminate described in Patent Document 1. The lid laminate described in Patent Document 1 is a lid laminate that includes a base layer, a heat seal layer provided on one side of the base layer, and a content adhesion prevention layer provided on the side of the heat seal layer opposite the base layer, in which the content adhesion prevention layer is a porous layer having a three-dimensional network structure formed by the adhesion of hydrophobic oxide fine particles having an average particle size of 3 to 100 nm.
[0005] Incidentally, the above-mentioned contents need to be protected from oxygen, water vapor, light, etc., and the lid of the package containing this type of content is also required to have barrier properties. In the lid laminate described in Patent Document 1, an aluminum foil having a thickness of 15 μm is exemplified as the barrier layer (see paragraphs
[0038] to
[0040] ). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 4348401 Summary of the Invention [Problem to be solved by the invention]
[0007] In recent years, advances in refrigeration technology have made it possible to transport food long distances. However, during long distance transport, food is exposed to vibrations from the road surface and truck engines for long periods of time, so if the sealing is not uniform, there is a concern that the contents will leak from weak sealing parts. Therefore, it is necessary to apply a sufficient amount of heat during heat sealing in order to seal the entire package uniformly.
[0008] However, in the lid laminate described in Patent Document 1, an aluminum foil having a thickness of 15 μm serves as a barrier layer. Therefore, when a lid made of the lid laminate is heat-sealed to a container using the heat seal layer, a large amount of heat is transmitted to the contents adhesion prevention layer, which may cause thermal damage to the contents adhesion prevention layer and result in a decrease in the contents adhesion prevention performance.
[0009] An object of the present invention is to provide a lid laminate that can suppress a decrease in the ability to prevent the contents from adhering to a container when the lid is heat-sealed to the container. [Means for solving the problem]
[0010] In order to achieve the above object, the present invention comprises the following aspects. 1) A lid laminate for producing a lid that is heat-sealed to the periphery of an opening of a container so as to cover the opening of the container containing the contents, A lid laminate comprising a base layer, a heat seal layer provided on one side of the base layer, and a content adhesion prevention layer provided on the surface of the heat seal layer opposite to the base layer side, the base layer being formed of a base resin layer and a barrier layer provided on one side of the base resin layer, the barrier layer being formed of a vapor deposition film having a thickness of 0.02 to 2 μm and made of a metal or metal oxide, and the content adhesion prevention layer being formed of hydrophobic fine particles attached to the surface of the heat seal layer.
[0011] 2) The lid laminate according to 1) above, wherein the heat seal layer is formed from a hot melt resin.
[0012] 3) The lid laminate according to 1) above, wherein a stress relaxation layer is interposed between the base layer and the heat seal layer.
[0013] 4) The lid laminate according to 1) above, wherein the tensile breaking strength in the machine direction (MD) and the tensile breaking strength in the transverse direction (TD) of the base material layer are both 200 to 350 MPa, and the tensile breaking elongation in the machine direction (MD) and the tensile breaking elongation in the transverse direction (TD) of the base material layer are both 100 to 200%.
[0014] 5) The average particle size of the hydrophobic fine particles in the contents adhesion prevention layer is 80 to 7000 nm, and the adhesion amount of the hydrophobic fine particles is 0.3 to 3 g / m 2 The laminated material for lids according to the above 1),
[0015] 6) The lid laminate according to 5) above, wherein the hydrophobic fine particles of the contents adhesion prevention layer are made of hydrophobic wet silica fine particles, and the average particle size of the hydrophobic wet silica fine particles is 1500 to 3500 nm.
[0016] 7) The hydrophobic fine particles of the contents adhesion prevention layer are made of hydrophobic wet silica fine particles, and the adhesion amount of the hydrophobic wet silica fine particles is 0.3 to 0.9 g / m 2 The laminated material for lids according to 5) above,
[0017] 8) A package in which contents are placed in a container having a peripheral wall portion and a bottom wall portion and an opening surrounded by the upper end portion of the peripheral wall portion, and the peripheral portion of a lid material made of a lid material laminate described in any one of 1) to 7) above is heat-sealed to the peripheral portion of the opening of the container by using a heat seal layer of the lid material.
[0018] 9) The package described in 8) above, wherein an outward flange portion is formed at the upper end of the peripheral wall portion of the container, a step portion is present on the upper surface of the flange portion, and the peripheral portion of the lid material is heat-sealed to the outward flange portion by utilizing a heat seal layer of the lid material. Effect of the Invention
[0019] According to the above 1) to 7) laminated lid materials, in a package using a lid made of the laminated lid material, the function of the contents adhesion prevention layer can prevent adhesion of contents to the inner surface of the lid.
[0020] Moreover, since the thickness of the barrier layer of the base layer is 2 μm or less, it is possible to reduce the heat transmission to the content adhesion prevention layer when the lid is heat-sealed to the container while maintaining the barrier properties, and to suppress thermal damage to the content adhesion prevention layer. Also, since the thickness of the barrier layer of the base layer is 2 μm or less, it is possible to suppress the detachment of the hydrophobic fine particles that form the content adhesion prevention layer due to the static electricity charged in the hydrophobic fine particles that form the content adhesion prevention layer being discharged to the barrier layer. Furthermore, since the thickness of the barrier layer of the base layer is 0.02 μm or more, the lid made of the lid laminate can effectively suppress the transmission of light, oxygen gas, water vapor, etc.
[0021] According to the lid laminate of the above 2), when a lid made of the lid laminate is heat-sealed to the periphery of the opening of a container, sufficient seal strength can be obtained with a relatively small amount of heat. Therefore, the amount of heat transferred to the content adhesion prevention layer during heat sealing can be reduced, and heat damage to the content adhesion prevention layer can be effectively suppressed.
[0022] Furthermore, when a lid made of the lid laminate described above in 2) is heat-sealed to a container, this can be done at a relatively low temperature, which reduces the thermal history of the base resin layer and the barrier layer and prevents the lid from breaking due to deterioration.
[0023] According to the above 3) laminated lid material, the stress relaxation layer can maintain the sealing strength of the lid made of the laminated lid material to the container even when it is subjected to vibration during transportation or when the atmospheric pressure changes. Furthermore, the stress relaxation layer can suppress the hydrophobic fine particles of the content adhesion prevention layer from falling off even when the lid made of the laminated lid material is subjected to external stress, thereby preventing a decrease in the content adhesion prevention performance.
[0024] According to the lid laminate of 4) above, the tensile breaking strength in the machine direction (MD) and the tensile breaking strength in the transverse direction (TD) of the base resin layer of the base material layer are both 200MPa or more, and the tensile breaking elongation in the machine direction (MD) and the tensile breaking elongation in the transverse direction (TD) of the base resin layer are both 100% or more, so that a lid that is difficult to deform or break can be obtained. Moreover, the tensile breaking strength in the machine direction (MD) and the tensile breaking strength in the transverse direction (TD) of the base resin layer of the base material layer are both 350MPa or less, and the tensile breaking elongation in the machine direction (MD) and the tensile breaking elongation in the transverse direction (TD) of the base resin layer are both 200% or less, so that when the lid laminate is punched to make a lid that matches the shape of the opening of a container, cutting defects such as stringing are suppressed.
[0025] According to the above 5) to 7) laminated materials for lids, the contents adhesion preventing layer has excellent contents adhesion preventing performance.
[0026] According to the above 6) lid laminate, the hydrophobic fine particles of the content adhesion prevention layer are made of hydrophobic wet silica fine particles, so that the adhesion to the heat seal layer is excellent and the content adhesion is less likely to fall off from the heat seal layer than when hydrophobic dry silica fine particles with a small particle size are used. Moreover, the hydrophobicity after heat sealing is less likely to be lost than when hydrophobic dry silica fine particles are used. However, if the average particle size of the hydrophobic wet silica fine particles is less than 1500 nm, the number of hydrophobic wet silica fine particles increases and they tend to aggregate when the adhesion amount is the same, which may result in a larger area of the area where the hydrophobic wet silica fine particles do not exist, and the content adhesion prevention property may decrease. Also, if the average particle size of the hydrophobic wet silica fine particles exceeds 3500 nm, the particle size may become too large and the adhesion to the heat seal layer may decrease. [Brief description of the drawings]
[0027] [Figure 1] FIG. 2 is an enlarged vertical cross-sectional view of a capping laminate according to the invention; [Diagram 2] 1 is a perspective view of an embodiment of a package using a lid formed from the lid laminate of the present invention; FIG. [Diagram 3] 3 is a partially enlarged vertical sectional view showing a portion of the packaging body of FIG. 2 on an enlarged scale. [Figure 4] FIG. 11 is a perspective view of another embodiment of a package container using a lid formed from the lid laminate of the present invention. [Diagram 5] 5 is an enlarged front view showing a part of the flange portion of the container in FIG. 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] Hereinafter, embodiments of the present invention will be described with reference to the drawings. However, the technical scope of the present invention is not limited to the embodiments shown in the drawings.
[0029] FIG. 1 shows a lid laminate according to the present invention, and FIGS. 2 and 3 show an embodiment of a package using a lid formed from the lid laminate of FIG.
[0030] In FIG. 1, the lid laminate (10) is made of a composite material in which a protective resin layer (11), a base layer (12) consisting of a base resin layer (12A) and a barrier layer (12B), an anchor coat layer (13), a stress relaxation layer (14), a heat seal layer (15), and a content adhesion prevention layer (16) are laminated in this order from one side of the lid laminate (10).
[0031] 2 and 3 show an example of a package using a lid made of the lid laminate (10).
[0032] 2 and 3, the package (1) is made of a container (2) that opens upward and contains the contents (C), and a lid (3). The lid (3) made of a lid laminate (10) is in the form of a flat sheet, with a protective resin layer (11) on its outer surface and a heat seal layer (15) on its inner surface. The lid (3) is placed on the upper end of the container (2) so as to close the opening, and is heat sealed to an outward flange portion (21) provided on the periphery of the opening of the container (2) by using the heat seal layer (15).
[0033] The contents (C) are semi-solid (fluid) or liquid contents (C), such as milk and dairy products (unprocessed and processed), such as cream and yogurt, liquid foods, such as soups and baby foods, and condiments, such as sauces and dressings.
[0034] Each of the layers (11) to (16) of the lid laminate (10) will now be described in detail.
[0035] [Protective resin layer (11)] The protective resin layer (11) constitutes the outermost surface of the lid (3) made of the lid laminate (10) and prevents the lid (3) from breaking, and also prevents the barrier layer (12B) from being scratched due to friction and from being corroded by condensation. The thickness of the protective resin layer (11) is preferably 1 to 20 μm.
[0036] The protective resin layer (11) is composed of various known overcoat agents and / or synthetic resin films.
[0037] Examples of the overcoat agent include polyurethane resin, polyester polyurethane resin, acrylic polyurethane resin, cellulose resin, epoxy resin, fluororesin, etc. The overcoat agent is preferably applied to the base layer (12) after the anchor coat layer is formed.
[0038] As the synthetic resin film, for example, a non-stretched film or a biaxially stretched film made of polyolefin, polyester, fluororesin, etc. is used. Examples of polyolefin include high density polyethylene (HDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE), homopolypropylene (hPP), propylene-ethylene random copolymer (rPP), propylene-ethylene block copolymer (bPP), etc. Examples of polyester include polyethylene terephthalate (PET), polyethylene naphthalate (PEN), and polybutylene terephthalate (PBT). The protective resin layer (11) made of a synthetic resin film may be a combination of two or more synthetic resin films of the same or different types. The protective resin layer (11) made of a synthetic resin film is formed by attaching the above-mentioned synthetic resin films with an adhesive.
[0039] The protective resin layer (11) may also be formed by combining an overcoat agent and a synthetic resin film. In that case, it is preferable to apply the overcoat agent to the outside of the synthetic resin film and to configure the outermost surface of the protective resin layer (11) with the overcoat layer.
[0040] A printed ink layer may be formed between the protective resin layer (11) and the base layer (12). The printed ink layer is composed of at least one of letters, figures, symbols, and patterns, and displays information about the contents of the package (1) in which the lid (3) made of the lid laminate (10) is used, or improves the design. When a printed ink layer is formed between the barrier layer (12) and the protective resin layer (11), a transparent protective resin layer (11) is used so that it can be seen from the outside.
[0041] [Base material layer (12)] In order to obtain a lid (3) that is resistant to deformation or breakage when a package (1) using the lid (3) made of the lid laminate (10) is transported, the base resin layer (12A) of the base layer (12) preferably has a tensile breaking strength in the machine direction (MD) and a tensile breaking strength in the transverse direction (TD) of 200 MPa or more, and a tensile breaking elongation in the machine direction (MD) and a tensile breaking elongation in the transverse direction (TD) of 100% or more. A lid (3) that is resistant to deformation or breakage suppresses the detachment of hydrophobic fine particles (161) that form the content adhesion prevention layer (16), which will be described later, and suppresses a decrease in the content adhesion prevention performance of the content adhesion prevention layer (16). In addition, in order to prevent cutting defects such as stringing from occurring when the lid laminate (10) is punched to make a lid (3) that matches the shape of the opening of the container (2), it is preferable that the base resin layer (12A) has a tensile breaking strength in the machine direction (MD) and a tensile breaking strength in the transverse direction (TD) of 350 MPa or less and a tensile breaking elongation in the machine direction (MD) and a tensile breaking elongation in the transverse direction (TD) of 200% or less.
[0042] As the base resin layer (12A), it is preferable to use a polyester film made of polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), etc., a polyolefin film such as a polyethylene resin or a polypropylene resin, or a fluororesin film having a thickness of 8 to 30 μm. If the thickness of the base resin layer (12A) is less than 8 μm, the strength of the base resin layer (12A) cannot be sufficiently ensured, making it difficult to form a uniform deposition film on the surface, and if it exceeds 30 μm, heat is not easily transferred to the heat seal layer (15), so more heat needs to be applied during heat sealing, which may have an adverse effect on the content adhesion prevention layer (16). In particular, it is preferable to use a biaxially stretched film with high crystallinity, taking into account the strength and the temperature applied during sealing.
[0043] The barrier layer (12B) of the base layer (12) is a layer that protects the contents of the package (1) using the lid (3) made of the lid laminate (10) from gas, water vapor, light, etc., and has a thickness of 0.02 to 2 μm, preferably 0.03 to 0.3 μm. If the thickness of the barrier layer (12B) is less than 0.02 μm, the lid (3) made of the lid laminate (10) cannot effectively suppress the transmission of light, oxygen gas, water vapor, etc., and if it exceeds 2 μm, the amount of heat transferred to the contents adhesion prevention layer (16) during heat sealing of the lid (3) made of the lid laminate (10) to the container (2) increases, and the entire contents adhesion prevention layer (16) receives relatively large heat damage, resulting in a decrease in the contents adhesion prevention performance. Furthermore, if the thickness of the barrier layer (12B) exceeds 2 μm, the hydrophobic fine particles that form the contents adhesion prevention layer (16) are likely to fall off due to the static electricity charged to the hydrophobic fine particles described below being discharged to the barrier layer (12B).
[0044] The barrier layer (12B) is produced by forming a vapor deposition film on one side of the base resin layer (12A) using a metal such as aluminum, gold, silver, copper, or titanium, or a semi-metal such as silicon, or an oxide of the above metal or semi-metal, by a PVD method or a CVD method.
[0045] In addition, in the base material layer (12), it is preferable that the barrier layer (12B) is arranged on the protective resin layer (11) side and the base material resin layer (12A) is arranged on the stress relaxation layer (14) side, since this can reduce the transmission of heat to the entire contents adhesion prevention layer (16).
[0046] [Anchor coat layer (13)] The anchor coat layer (13) is interposed between the base layer (12) and the stress relaxation layer (14) to increase the adhesion between the layers (12) and (14) and prevent delamination. The anchor coat layer (13) is formed of a cellulose resin such as nitrocellulose or ethylcellulose, a chlorinated polyethylene resin, an acrylic resin such as polymethyl methacrylate, a vinyl chloride-vinyl acetate copolymer, a thermoplastic polyester resin, or a polyurethane resin. As the polyurethane resin, various known polyurethane resin adhesives can be used, and in particular, it is preferable to use a two-component curing polyether polyurethane resin adhesive or a two-component curing polyester polyurethane resin adhesive. The thickness of the anchor coat layer (13) is not particularly limited, but is preferably 0.1 to 5 μm.
[0047] [Stress relief layer (14)] The stress relaxation layer (14) relieves stress acting on the base layer (12) including the barrier layer (12B), and has a thickness of preferably 10 μm to 50 μm, more preferably 15 to 40 μm. The stress relaxation layer (14) is preferably made of a polyolefin resin such as polyethylene, ethylene-α-olefin copolymer, or polypropylene, an ethylene-vinyl acetate copolymer resin (EVA), a polyester resin, or a polyurethane resin. In particular, it is preferable to use LDPE, LLDPE, or a mixed resin of LDPE and LLDPE. [Heat seal layer (15)]
[0048] The heat seal layer (15) is a layer for heat sealing the lid (3) made of the lid laminate (10) to the flange portion (21) around the opening edge of the container (2). The material is not particularly limited as long as it has good adhesion to the stress relief layer (14) and the flange portion (21) of the container (2). For example, in the case of a lid (3) for a package (1) containing yogurt and in which the container (2) has a low-density polyethylene layer formed on the inner surface, the heat seal layer (15) is preferably made of a hot melt resin containing ethylene-vinyl acetate copolymer resin (EVA), olefin polymer, wax, tackifier, and other additives. The amount of hot melt resin used is 10 to 25 g / m. 2 A specific example of the composition of the hot melt resin is as follows: Ethylene vinyl acetate copolymer: 2 to 25% by mass Olefin polymer: 10 to 40% by mass Wax: 35-65% by weight Tackifier: 3 to 25% by mass It is.
[0049] [Contents adhesion prevention layer (16)] The content adhesion prevention layer (16) constitutes the inner surface of the lid (3) made of the lid laminate (10), and is a layer that imparts a content adhesion prevention function, and is made of a large number of hydrophobic fine particles (161) attached to the surface of the heat seal layer (15). The average particle diameter of the hydrophobic fine particles (161) is preferably 80 to 7000 nm. If the average particle diameter of the hydrophobic fine particles (161) is too small, the hydrophobic fine particles (161) are likely to be attached to the surface of the heat seal layer (15) so as to fill in the unevenness of the surface, which may reduce the water repellency, and if the average particle diameter is too large, the hydrophobic fine particles (161) are likely to fall off. The adhesion amount of the hydrophobic fine particles (161) in the content adhesion prevention layer (16) is 0.3 to 3 g / m 2 If the amount of adhesion is too small, sufficient water repellency cannot be obtained, whereas if the amount of adhesion is too large, the hydrophobic fine particles (161) tend to fall off.
[0050] Examples of the hydrophobic fine particles (161) include hydrophobic inorganic fine particles such as hydrophobic silica fine particles, alumina fine particles, calcium oxide fine particles, calcium carbonate fine particles, calcium sulfate fine particles, calcium silicate fine particles, etc. Among these hydrophobic fine particles, it is preferable to use hydrophobic wet-type silica fine particles which are synthetic amorphous silica produced by a wet method and have been given hydrophobicity by chemically reacting an organic silicon compound with the hydroxyl groups on the surface of the wet-type silica fine particles.
[0051] Compared with dry silica, wet silica has more surface silanol groups, and therefore even after the surface is hydrophobized with silanes or silicones, wet silica shows superior water repellency and hydrophobicity to dry silica. Also, compared with dry silica particles, which have secondary particles as the smallest unit, which are aggregates of primary particles without pores, wet silica particles not only have a larger particle size, but also a larger specific surface area relative to the particle size, a larger pore volume, and a larger oil absorption. These factors are also considered to contribute greatly to the improvement of the performance of the adhesion prevention layer.
[0052] In order to effectively utilize the characteristics of the wet silica, it is preferable to use wet silica particles having a pore volume of 0.4 ml / 100 g or more and an oil absorption of 50 ml / 100 g or more, preferably 150 ml / 100 g or more. If the oil absorption is less than 50 ml / 100 g, the ability to rapidly adsorb a sufficient amount of low melting point and low molecular weight components contained in the heat seal layer (15) when it melts is poor, and the effect of improving the heat resistance of the content adhesion prevention layer (16) cannot be fully achieved. The upper limit of the oil absorption is not particularly limited, but wet silica produced by a wet method having an oil absorption of 250 to 350 ml / 100 g or less is sufficient, and there is no need to select and use a special wet silica having an oil absorption greater than that. Rather, the disadvantage of inviting increased costs is greater.
[0053] The average particle size of the hydrophobic wet silica microparticles is larger than that of the hydrophobic dry silica microparticles, so that the hydrophobic wet silica microparticles have better adhesion to the heat seal layer (15) and are less likely to fall off from the heat seal layer (15) than the hydrophobic dry silica microparticles. Moreover, compared to the hydrophobic dry silica microparticles, the influence of heat during heat sealing and drying is suppressed, and the hydrophobic function of the silica microparticles is maintained even after heat sealing. However, if the average particle size of the hydrophobic wet silica microparticles is less than 1500 nm, the number of hydrophobic wet silica microparticles increases and they tend to aggregate when the adhesion amount is the same, and as a result, the area of the area where the hydrophobic wet silica microparticles do not exist increases, and there is a risk that the ability to prevent adhesion of contents decreases. Also, if the average particle size of the hydrophobic wet silica microparticles exceeds 3500 nm, the particle size becomes too large and the adhesion to the heat seal layer (15) decreases.
[0054] Since the hydrophobic wet silica microparticles are porous, the low-viscosity, low-melting-point components of the heat seal layer (15) that melt during heat sealing can easily penetrate through the contact points, and as a result, a part of the content adhesion prevention layer (16) is integrated with the heat seal layer (15), preventing the hydrophobic wet silica microparticles from falling off. When hydrophobic wet silica microparticles are used, the adhesion amount is 0.3 to 0.9 g / m 2 It is preferable that:
[0055] The content adhesion prevention layer (16) can be formed, for example, by preparing a dispersion liquid in which hydrophobic fine particles (161) are dispersed in a solvent, and applying the dispersion liquid to the surface of the heat seal layer (15). As the solvent used to prepare the dispersion liquid, it is preferable to use an organic solvent in order to ensure the fixation and adhesion of the hydrophobic fine particles (161) to the heat seal layer (15), and it is more preferable to use a solvent having a polar group. Among these, alcohol is particularly preferably used. More specifically, the content adhesion prevention layer (16) can be formed by applying a coating liquid prepared by dispersing hydrophobic fine particles (161) in a solvent having a polar group to a surface of the heat seal layer (15) in a dry weight (adhesion amount) of 0.3 to 3.0 g / m. 2After that, the coating is applied to the surface of the heat seal layer (15) so as to form the coating, and then the coating is dried at a temperature of 80 to 140° C. for a time of 5 to 30 seconds.
[0056] 4 and 5 show another embodiment of a container having an opening closed by a lid formed from the lid laminate (10) according to the present invention.
[0057] In Figures 4 and 5, the container (5) is used as a package for, for example, yogurt, and is composed of a tapered cylindrical peripheral wall portion (6) and a bottom wall portion (7) that closes the lower end opening of the peripheral wall portion (6).
[0058] The peripheral wall portion (6) is produced by forming a generally sector-shaped body blank, for example paper with one side covered with a low-density polyethylene layer, into a tapered tube shape with the low-density polyethylene layer on the inside, and then joining both end edges of the body blank together while overlapping each other. Therefore, the peripheral wall portion (6) has an overlap portion (61) extending along its height direction. The peripheral edge of the upper opening of the peripheral wall portion (6) is provided with an outward flange portion (8) formed by bending a certain length of the upper end of the peripheral wall portion (6) outward. The flange portion (8) has an overlap portion (81) continuing to the overlap portion (61) of the peripheral wall portion (6), and the presence of the overlap portion (81) forms a step portion (82) in the flange portion (8) as shown in FIG. 5.
[0059] The bottom wall portion (7) is made by forming a generally sector-shaped body blank, for example made of paper with one side covered with a low-density polyethylene layer, into a cap shape consisting of a horizontal portion and a hanging portion integrally formed on the periphery of the horizontal portion. The peripheral surface of the hanging portion of the bottom wall portion (7) is joined to the inner peripheral surface of the lower end of the peripheral wall portion (6), thereby integrating the peripheral wall portion (6) and the bottom wall portion (7).
[0060] When a lid material made of the lid laminate (10) of the present invention is heat-sealed to the upper surface of the flange portion (8) of the peripheral wall portion (6) of the above-mentioned container (5) using the heat seal layer (15), excellent sealing performance is obtained because the heat seal layer (15) is made of a hot melt resin and the barrier layer (12B) is made of a vapor-deposited film made of metal or metal oxide and has a thickness of 0.02 to 2 μm, and thus sealing is performed along the step portion (82).
[0061] Next, examples of the present invention and comparative examples will be described.
[0062] [Example 1] and [Example 7] As the base resin layer (12A), a biaxially oriented polyethylene terephthalate film (PET) with a thickness of 12 μm and a tensile breaking strength of 220 MPa in the machine direction (MD), a tensile breaking strength of 230 MPa in the transverse direction (TD), a tensile breaking elongation of 110% in the machine direction (MD), and a tensile breaking elongation of 110% in the transverse direction (TD) was used. A barrier layer (12B) made of an aluminum vapor deposition film with a thickness of 0.1 μm was formed on one side of the base resin layer (12A) by a vacuum deposition method using a plasma-treated electrode by adjusting the treatment time, voltage, pressure, etc., to obtain the base layer (12).
[0063] Next, a biaxially oriented PET film having a thickness of 12 μm was laminated on the surface of the barrier layer (12B) of the base layer (12) via an ester-based two-component curing adhesive, and dry laminated by sandwiching and pressing between a rubber nip roll and a laminating roll. After that, an aging treatment was performed at 40° C. for 3 days to form a protective layer (11).
[0064] Next, a urethane anchor coating agent was applied to the surface of the base resin layer (12A) of the base layer (12) in an amount of 0.2 g / m 2 After forming an anchor coat layer (13) by coating in such a manner that the thickness of the resin becomes 20 μm, a stress relaxation layer (14) was formed by extrusion laminating a low density polyethylene (LDPE) resin using a T-die.
[0065] Next, a hot melt resin having a composition of 45 wt% EVA, 45 wt% polyethylene wax, and 10 wt% tackifier (a resin copolymerized with terpene monomer and phenol) was applied to the surface of the stress relaxation layer (14) in a weight of 18 g / m. 2 The heat seal layer (15) was formed by gravicoating the film so as to obtain the following: Thereafter, a dispersion liquid obtained by dispersing hydrophobic wet silica fine particles (161) having an average particle size of 2400 nm in an ethanol solvent at a dispersion concentration of 5% by mass was applied to the surface of the heat seal layer (15) by a gravure coating method, and then dried at a temperature of 100°C for a time of 15 seconds, thereby forming a contents adhesion prevention layer (16) made of hydrophobic wet silica fine particles (161) on the surface of the heat seal layer (15). The adhesion amount of the hydrophobic wet silica fine particles (161) after drying was 0.6 g / m 2 It was.
[0066] In this way, a lid laminate (10) was produced.
[0067] [Example 2] A lid laminate (10) was produced in the same manner as in Example 1, except that the thickness of the barrier layer (12B) made of an aluminum vapor deposition film was set to 0.02 μm.
[0068] [Example 3] A lid laminate (10) was produced in the same manner as in Example 1, except that the thickness of the barrier layer (12B) made of an aluminum vapor deposition film was set to 0.5 μm.
[0069] [Example 4] A lid laminate (10) was produced in the same manner as in Example 1, except that the thickness of the barrier layer (12B) made of an aluminum vapor deposition film was set to 1 μm.
[0070] [Example 5] A lid laminate (10) was produced in the same manner as in Example 1, except that the thickness of the barrier layer (12B) made of an aluminum vapor deposition film was set to 1.5 μm.
[0071] [Example 6] A lid laminate (10) was produced in the same manner as in Example 1, except that a barrier layer (12B) made of a 0.1 μm-thick SiO2 vapor deposition film was formed on one side of the base resin layer (12A) by adjusting the treatment time, voltage, pressure, etc., using a vacuum deposition method using a plasma-treated electrode.
[0072] [Example 8] A lid laminate (10) was produced in the same manner as in Example 1, except that the average particle size of the hydrophobic wet silica particles (161) forming the contents adhesion prevention layer (16) was 80 nm.
[0073] [Example 9] A lid laminate (10) was prepared in the same manner as in Example 1, except that the average particle size of the hydrophobic wet silica particles (161) forming the contents adhesion prevention layer (16) was 100 nm.
[0074] [Example 10] A lid laminate (10) was produced in the same manner as in Example 1, except that the average particle size of the hydrophobic wet silica particles (161) forming the contents adhesion prevention layer (16) was set to 500 nm.
[0075] [Example 11] A lid laminate (10) was prepared in the same manner as in Example 1, except that the average particle size of the hydrophobic wet silica particles (161) forming the contents adhesion prevention layer (16) was set to 1000 nm.
[0076] [Example 12] A lid laminate (10) was prepared in the same manner as in Example 1, except that the average particle size of the hydrophobic wet silica particles (161) forming the contents adhesion prevention layer (16) was set to 5000 nm.
[0077] [Example 13] A lid laminate (10) was prepared in the same manner as in Example 1, except that the average particle size of the hydrophobic wet silica particles (161) forming the contents adhesion prevention layer (16) was set to 7000 nm.
[0078] [Example 14] The amount of hydrophobic wet silica particles (161) attached to the content adhesion prevention layer (16) after drying is 0.1 g / m 2 A lid laminate (10) was produced in the same manner as in Example 1, except that:
[0079] [Example 15] The amount of hydrophobic wet silica particles (161) attached to the content adhesion prevention layer (16) after drying is 0.3 g / m 2 A lid laminate (10) was produced in the same manner as in Example 1, except that:
[0080] [Example 16] The amount of hydrophobic wet silica particles (161) attached to the content adhesion prevention layer (16) after drying is 1.8 g / m 2 A lid laminate (10) was produced in the same manner as in Example 1, except that:
[0081] [Example 17] The amount of hydrophobic wet silica particles (161) attached to the content adhesion prevention layer (16) after drying is 2.4 g / m 2 A lid laminate (10) was produced in the same manner as in Example 1, except that:
[0082] [Example 18] A lid laminate (10) was prepared in the same manner as in Example 1, except that a biaxially oriented polyethylene terephthalate film (PET) having a thickness of 12 μm, a tensile breaking strength in the machine direction (MD) of 190 MPa, a tensile breaking strength in the transverse direction (TD) of 190 MPa, a tensile breaking elongation in the machine direction (MD) of 140%, and a tensile breaking elongation in the transverse direction (TD) of 150%, was used as the base resin layer (12A), and the average particle size of the hydrophobic wet silica microparticles (161) forming the content adhesion prevention layer (16) was set to 2000 nm.
[0083] [Example 19] A lid laminate (10) was prepared in the same manner as in Example 1, except that a biaxially oriented polyethylene terephthalate film (PET) having a thickness of 12 μm and a tensile breaking elongation of 95% in the machine direction (MD) and 100% in the transverse direction (TD) was used as the base resin layer (12A), and the average particle size of the hydrophobic wet silica microparticles (161) forming the contents adhesion prevention layer (16) was set to 1700 nm.
[0084] [Example 20] Hot melt resin with a weight of 0.2 g / m 2 A covering laminate (10) was produced in the same manner as in Example 1, except that the heat seal layer (15) was formed by gravicoating so as to form the covering laminate (10).
[0085] [Example 21] Hot melt resin with a weight of 3g / m 2 A covering laminate (10) was produced in the same manner as in Example 1, except that the heat seal layer (15) was formed by gravicoating so as to form the covering laminate (10).
[0086] [Example 22] Hot melt resin, weight per unit area: 35g / m 2 A covering laminate (10) was produced in the same manner as in Example 1, except that the heat seal layer (15) was formed by gravicoating so as to form the covering laminate (10).
[0087] [Example 23] Hot melt resin with a weight of 45g / m 2 A covering laminate (10) was produced in the same manner as in Example 1, except that the heat seal layer (15) was formed by gravicoating so as to form the covering laminate (10).
[0088] [Example 24] A lid laminate (10) was prepared in the same manner as in Example 1, except that a 30 μm thick polyethylene sealant film was used as the heat seal layer (15) and was adhered to the surface of the stress relief layer (14) via an adhesive.
[0089] [Example 25] A lid laminate (10) was prepared in the same manner as in Example 1, except that the average particle size of the hydrophobic wet silica particles (161) forming the contents adhesion prevention layer (16) was set to 1500 nm.
[0090] [Example 26] A lid laminate (10) was prepared in the same manner as in Example 1, except that the average particle size of the hydrophobic wet silica particles (161) forming the contents adhesion prevention layer (16) was set to 3000 nm.
[0091] [Comparative Example 1] A lid laminate was prepared in the same manner as in Example 1, except that the thickness of the barrier layer made of an aluminum vapor deposition film was set to 0.01 μm.
[0092] [Comparative Example 2] A lid laminate was prepared in the same manner as in Example 1, except that the thickness of the barrier layer made of an aluminum vapor deposition film was set to 2.5 μm.
[0093] The configurations of the lid laminate materials of Examples 1 to 26 and Comparative Examples 1 and 2 are shown in Table 1 below.
[0094] [Table 1]
[0095] In Table 1, HM indicates hot melt resin, and PE-F indicates polyethylene sealant film. In addition, with regard to the basis weight and thickness of the heat seal layer in Table 1, Examples 1 to 23, 25, and 26 and Comparative Examples 1 and 2 indicate the basis weight, and Example 24 indicates the thickness.
[0096] [Evaluation test] Prevents contents from sticking A droplet of aloe yogurt (trademark "Morinaga Aloe Yogurt" manufactured by Morinaga Milk Industry Co., Ltd.) of about 0.5 ml was dropped onto the surface of the contents adhesion prevention layer of each lid laminate, and the inclination angle at which the droplet started to roll when each lid laminate was slowly tilted was measured. Based on the measurement results, the following criteria were used for evaluation. ◎: 15 degrees or less, ○: 16 degrees or more and 25 degrees or less, △: 26 degrees or more and 30 degrees or less, ×: 31 degrees or more, with ◎, ○, and △ being pass. Hydrophobic particle adhesion A weight (500 g) wrapped with black cloth was placed on the surface of the content adhesion prevention layer of each lid laminate, and the surface of the cloth was rubbed slowly for a length of 200 m, and the presence or absence of fine particles attached to the surface of the cloth was visually observed. The amount of transferred fine particles (amount of peeling) to the black cloth was then evaluated according to the following criteria. ⊚: Almost no adhesion, ◯: slight adhesion, △: adhesion that is within an acceptable range, ×: significant adhesion, with ⊚, ◯ and △ being pass marks. Gas barrier properties The gas barrier properties were determined from the oxygen permeability and water vapor permeability.
[0097] Oxygen permeability was measured at a temperature and humidity of 20°C / 10%Rh according to the method specified in JIS K7126-2.Water vapor permeability was measured at a temperature and humidity of 40°C / 90%Rh according to the method specified in JIS K7129B.
[0098] The evaluation criteria are as follows, with ⊚ and ◯ being acceptable. ◎: Oxygen permeability is 60.0ml / m under 20℃ and 0% RH environment 2 ·day·MPa or less Water vapor permeability is 6.0g / m at 40℃ and 90% RH. 2 ·day or less ○: Oxygen permeability is 60.0ml / m under 20℃ and 0% RH environment 2 ·day·MPa Exceeds 100.0ml / m 2 ·day·MPa or less Water vapor permeability is 6.0g / m at 40℃ and 90% RH. 2 ·day or less ×: Oxygen permeability is 100.0ml / m under 20℃ and 0% RH environment 2 ·day·MPa Water vapor permeability is 10.0g / m at 40℃ and 90% RH. 2 ·day super The evaluation results for adhesion prevention, adhesion and barrier properties are shown in Table 2.
[0099] [Table 2] [Industrial Applicability]
[0100] The laminated lid material of the present invention is suitable for use as a lid for packaging that hermetically packs dairy products, ice creams, and frozen foods as its contents. [Explanation of symbols]
[0101] (1):Packaging (2): Container (3): Lid (10): Laminated material for lid (11): Protective resin layer (12): Base material layer (12A): Base resin layer (12B): Barrier layer (13): Anchor coat layer (14): Stress relief layer (15): Heat seal layer (16): Contents adhesion prevention layer (161): Hydrophobic microparticles
Claims
1. A lid laminate for producing a lid that is heat-sealed to a periphery of an opening of a container so as to cover the opening of the container containing contents, comprising:
1. A lid laminate comprising: a base material layer; a heat seal layer provided on one side of the base material layer; and a content adhesion prevention layer provided on the surface of the heat seal layer opposite to the base material layer side, the base material layer being formed of a base material resin layer and a barrier layer provided on one side of the base material resin layer, the barrier layer being formed of a vapor deposition film having a thickness of 0.02 to 2 μm and made of a metal or a metal oxide, and the content adhesion prevention layer being formed of hydrophobic fine particles attached to the surface of the heat seal layer.
2. 2. The lidding laminate of claim 1, wherein said heat seal layer is formed from a hot melt resin.
3. 2. The lid laminate of claim 1, further comprising a stress relief layer interposed between said base layer and said heat seal layer.
4. The tensile breaking strength in the machine direction (MD) and the tensile breaking strength in the transverse direction (TD) of the base material layer are both 200 to 350 MPa, and the tensile breaking elongation in the machine direction (MD) and the tensile breaking elongation in the transverse direction (TD) of the base material layer are both 100 to 200%. The lid laminate according to claim 1.
5. The average particle size of the hydrophobic fine particles in the contents adhesion prevention layer is 80 to 7000 nm, and the adhesion amount of the hydrophobic fine particles is 0.3 to 3 g / m 2 2. The lid laminate of claim 1, wherein
6. The lid laminate according to claim 5, wherein the hydrophobic fine particles of the content adhesion prevention layer are made of hydrophobic wet silica fine particles, and the average particle size of the hydrophobic wet silica fine particles is 1500 to 3500 nm.
7. The hydrophobic fine particles of the contents adhesion prevention layer are made of hydrophobic wet silica fine particles, and the adhesion amount of the hydrophobic wet silica fine particles is 0.3 to 0.9 g / m 2 6. The lid laminate of claim 5, wherein
8. A package comprising a container having a peripheral wall and a bottom wall and an opening surrounded by an upper end of the peripheral wall, the contents being placed in the container, and the peripheral edge of a lid material made of the lid material laminate according to any one of claims 1 to 7 being heat-sealed to the peripheral edge of the opening of the container by utilizing a heat-seal layer of the lid material.
9. 9. The package according to claim 8, wherein an outward flange portion is formed at an upper end of the peripheral wall portion of the container, a step portion is present on an upper surface of the flange portion, and the peripheral portion of the lid material is heat-sealed to the outward flange portion by utilizing a heat seal layer of the lid material.
Citation Information
Patent Citations
Lid material
JP4348401B1